UNVEILING GENDER PERFORMATIVITY THROUGH MAKE OVER ADVERTISEMENT: : A CRITICAL DISCOURSE ANALYSIS - Tarisa Aura Salsabila (Language Horizon: Journal of Language Studies, 2024)
This article investigates how gender performativity is constructed and reinforced in beauty product advertisements, specifically analyzing Make Over brand ads on Instagram from 2023 to 2024. Using Judith Butler’s theory of gender performativity and Norman Fairclough’s three-dimensional Critical Discourse Analysis (CDA) framework, the study explores how linguistic features, discursive techniques, and social factors work together to shape and manipulate gendered messages in modern beauty marketing. Through a critical multimodal discourse analysis, the research shows how language, images, and social cues in these ads uphold traditional femininity, reinforce cultural norms, and reflect broader power structures and ideologies within the beauty industry. The findings contribute to theory by supporting Butler’s idea of gender as a socially performed construct and broadening CDA’s use in media discourse analysis. Practically, the study provides insights for advertisers, the beauty industry, and policymakers to promote more inclusive and diverse gender representations in advertising, aiming to challenge harmful stereotypes and foster healthier ideals of beauty and identity in the digital age.